HABITUATION AND DESHABITUATION OF ORIENTING RESPONSE IN DEPRESSIVE SUBJECTS - Miquel, Marta; García Merita, Mª Luisa; Fuentes, I.; Rojo, L. (Anales de Psicología / Annals of Psychology)
In this paper, are revised research about orienting response habituation/deshabituation in depressive subjects. ln this subjects, a little electrodermal responsivity appear when stimulus are administrated them, the orienting response decreases very quikly, and there aren't deshabituation in response to stimular change.It shows that sensitization process is alterated in depressive people.